POLA ASUH ORANG TUA YANG BERPOLIGAMI DALAM MENDIDIK AKHLAK ANAK (STUDI KASUS DI DESA V JEMENANG KECAMATAN RAMBANG DANGKU KABUPATEN MUARA ENIM) - Ririn Yunda Wati; Alimron Alimron; Abu Mansur; Sofyan Sofyan (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2021)
Parenting patterns of polygamy parents in educating children's morals (case study in V Jemenang Village, Rambang Dangku District, Muara Enim Regency). The formulation of the problem in this research is how is the parenting style of polygamy parents in educating children's morals (case study in Jemenang V village, Rambang Dangku district, Muara Enim Regency)? as well as what are the obstacles faced by polygamy parents in educating children's morals (case study in V Jemenang Village, Rambang Dangku District, Muara Enim Regency). The purpose of this study was to determine how parenting practices of polygamy parents in educating child morals in V Jemenang Village, Rambang Dangku District, Muara Enim Regency and to find out what are the obstacles faced by polygamy parents in educating child morals in V Jemenang Village, Rambang Dangku District, Muara District Enim. This research is a qualitative research. Data collection techniques in this study used interview, observation and documentation methods. Data analysis in this study uses data analysis from Miles and Huberman which includes data reduction, data display, and conclusion drawing or verification of data (conclusion drawing or verification). Based on the results of the study show that First, many ways or patterns of parenting that are used by parents who practice polygamy in educating children is the authoritarian parenting, democratic parenting, and permissive parenting, Second, the obstacles faced by parents who polygamy in educating child morals are , lack of economy so that the time between parent (father) and child is reduced, so that the lack of communication between child and parent, the sharing of affection so that the lack of affection felt by the child, parental attention is lacking so that the child falls into wrong promiscuity, and the rigors of the ego children have that makes it difficult for parents to educate children.